Hearing Impairment and Cognitive Decline in Older, Community-Dwelling Adults. (12th February 2019) - Alattar, Ali A; Bergstrom, Jaclyn; Laughlin, Gail A; Kritz-Silverstein, Donna; Richard, Erin L; Reas, Emilie T; Harris, Jeffrey P; Barrett-Connor, Elizabeth; McEvoy, Linda K
Abstract: Background: Hearing impairment is prevalent among older adults and has been identified as a risk factor for cognitive impairment and dementia. We evaluated the association of hearing impairment with long-term cognitive decline among community-dwelling older adults. Methods: A population-based longitudinal study of adults not using hearing aids who had hearing acuity and cognitive function assessed in 1992–1996, and were followed for a maximum of 24 years with up to five additional cognitive assessments. Hearing acuity was categorized based on pure-tone average (PTA) thresholds: normal (PTA ≤ 25 dB), mild impairment (PTA > 25–40 dB), moderate/severe impairment (PTA > 40 dB). Results: Of 1, 164 participants (mean age 73.5 years, 64% women), 580 (49.8%) had mild hearing impairment and 196 (16.8%) had moderate/severe hearing impairment. In fully adjusted models, hearing impairment was associated with steeper decline on the Mini-Mental State Examination (MMSE) (mild impairment β = −0.04, p = .01; moderate/severe impairment β = −0.08, p = .002) and Trails B (mild impairment β = 1.21, p = .003; moderate/severe impairment β = 2.16, p = .003). Associations did not differ by sex or apolipoprotein E (APOE) ϵ4 status and were not influenced by social engagement. The MMSE-hearing association was modified by education: mild hearing impairment was associated with steeper decline on the MMSE among participants without college education but not among those with college education. Moderate/severe hearing impairment was associated with steeper MMSE decline regardless of education level. Conclusions: Hearing impairment is associated with accelerated cognitive decline with age, and should be screened for routinely. Higher education may provide sufficient cognitive reserve to counter effects of mild, but not more severe, hearing impairment.